Ações de família no CPC/2015 : conceito e técnicas - Oliveira, Michelle Ivair Cavalcanti (2019)
The current Civil Procedure Code (Law 13.105/2015) established, in an unprecedented manner, specific procedure rules applicable to "family actions". However, even though it indicates the hypotheses of application, the determinative criteria for its use were not legally indicated, nor was its concept defined. Thus, based on a proposed semantic agreement, based on the relationship between Family Law and the current civil procedure paradigms, this dissertation is devoted to analyzing the mentioned special techniques, as well as whether they constitute a special procedure or deserve a different classification. Furthermore, it seeks to verify the applicability extension of the procedural rules of family actions, as well as its influence on objective material competence, adopting Chiovenda’s classification. Therefore, it observes whether the criteria of procedural rules are in line with the Brazilian civil procedure fundamental norms, especially equality and efficiency.